Effects of dietary vitamin E on the wound healing induced in Oreochromis niloticus - Iwashita, Marina Keiko Pieroni; Engracia Filho, Jair Rodini; Claudiano, Gustavo da Silva; Aguinaga, Jefferson Yunis; Ozório, Rodrigo Otavio de Almeida; Moraes, Julieta Rodini Engrácia de (Brazilian Journal of Veterinary Research and Animal Science, 2021)
In the present study, the effect of vitamin E supplementation 450 mg/kg diet was appraised in the process of induced wound healing in Nile tilapias Oreochromis niloticus. Fish were distributed into 18 tanks (10 fish each). Nine tanks were fed the non-supplemented diet and the other 9 tanks were fed 450 mg vitamin E for 60 days. Subsequently, the fish were anesthetized and the epidermis and dermis were surgically removed. The rate of cicatricial retraction and appearance of the wounds, and the histomorphometry of mucous cells, chromatophores, revascularization, inflammatory cells, presence of fibroblasts, collagen fibers, and scales were checked after 3-, 7-, 14-, 21-, and 28 days post-wounding. The retraction rate of the wound was significantly higher in the supplemented fish. The higher concentrations of inflammatory cells, mucous cells, and chromatophores, as well as the production and organization of collagen fibers, resulted in a higher retraction rate. We concluded that a dietary supplementation diet improves specific aspects of the cutaneous healing process in Nile tilapia fish.